Beach response due to the pressure equalization modules (PEM) system - Ab. Razak, Mohd. Shahrizal (2009)
Coastal erosion is a significant problem with dramatic effects on the coastline. There is an urgent need to introduce new and cost-effective measures that can mitigate the impacts on the shoreline. This study has been initiated to investigate the response of the beach at Teluk Cempedak due to the beach nourishment and Pressure Equalization Modules (PEM) system. The objectives of this study are the determination of closure depth and effectiveness of the system in treating the erosion process. The depth of closure was examined using both data from a series of beach profile surveys and from empirical formulae. The widely accepted Fixed Depth Change (FDC) method was explored and the hc before and after the installation of PEM system was investigated. The research found that multiple closure points can occur along the profile lines. The closure depth after the installation of PEM system was found to be deeper and the closure point is further seaward at the southern part of the beach. The Hellemeier’s equation over predict hc by 76 %, however it reveals that the equation is still robust in determining an upper limit of hc. The simplified equation was developed at Teluk Cempedak beach in predicting closure depth and can be equated to 0.98 times H0.137. From the survey data, it is found that after three years, the total sand volume and beach elevation are significantly higher in PEM areas. Generally, the result presented indicates the decreasing value of rate of erosion. Thus it revealed that PEM system is able to stimulate accretion of sand and yet slow down the erosion process. However, based on the sand volume distribution pattern, after three years, it is obviously seen that the accretion of sand occurring at the northern part while erosion process is taking place in the southern part of the beach. Based on the distribution pattern of bed elevation over the chainage, overall, the upper part of the beach is convex unlike earlier i.e before the installation of PEM system, where the beach was low and concave. This phenomena indicates that the system contribute to a significant accretion of sand and thus created a higher beach level at about 10 m to 55 m towards the sea. However, this trend only can be seen at a certain chainage. The PEM efficiency in terms of increment in bed elevation can only be observed at CH 400 till CH 800 while at CH 900 towards the south, the efficiency is decreasing. This shows that the accretion of sand is only occurring at the northern part and the beach is eroding at the southern part. Therefore, based on the available four years record of data, there is a certain part of the beach benefiting from the PEM system. However, some parts are still experiencing the erosion process.